1881 Nev. Stat. 19-20 - (:unkn) unknown (My University, 1881)
Ch. 7, § 1: Any person in this State, whether under the influence of liquor or otherwise, who shall, except in necessary self-defense, maliciously, wantonly or negligently discharge or cause to be discharged any pistol, gun or any other kind of firearm, in or upon any public street or thoroughfare, or in any theater, hall, store, hotel, saloon or any other place of public resort, shall be deemed guilty of a misdemeanor
Keywords: DISCHARGE